Endobronchial Lipoma: A Case Report - ElmustafaHassan, SalahEldin Mohamed; Murad, Ismail; Khalil, Gumaa Aboul Nasr (Gezira Journal of Health Sciences, 2015)
Endobronchial lipoma is a benign tumor of the large bronchi occurring in middle-aged men. The symptoms are those of obstructive pneumonitis mimicking bronchogenic carcinoma, and the result of delayed therapy may be bronchiectasis. Treatment includes local resection through a bronchoscope or a bronchotomy incision, or removal, if necessary, of the obstructed lobe or lung at thoracotomy. Smoking may be important in the pathogenesis of this tumor. Case :A 37 years old man presented with symptoms of asthma. X-ray showed unilateral inflation of the left lung. Flexible bronchoscope showed well circumscribed rounded mass in left main bronchus .CT scan raises the possibility of a benign intrabronchial mass. Surgical excision of the mass and subsequent histological examination confirmed the diagnosis of endobronchial lipoma. Discussion: Bronchoscopic resection should be considered as the first choice of treatment for endobronchial lipoma; however, surgical therapy is indicated for patients who show the possibility of a complicated malignant tumor, who have destructive peripheral lung disease, who have extrabronchial growth, or who may have technical difficulties during the bronchoscopic procedure